Faisons les courses! : le français en s'amusant. ([S.l.] : Eli, 2012)
"Faisons les courses !" helps consolidate and revise correct use of vocabulary and language structures related to shopping. Food and drink are presented in a fun shopping situation which allows students to widen their range of vocabulary and improve communication skills. (CEFR A1-A2) The game consists of a set of 66 photographic cards, 36 shopping lists with bingo cards on the reverse side and an instruction booklet. The instruction booklet contains game instructions, ideas for further activities, a food quiz, typical recipes and a wide range of idioms related to food.
Bevat: 66 fotokaartjes, 36 boodschappenlijstjes, handleiding.
Keywords: Frans -- Basisonderwijs